2021
DOI: 10.3390/ijerph18189604
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Lockdown on Agility, Explosive Power, and Speed-Endurance Capacity in Youth Soccer Players

Abstract: Our goal was to assess agility, explosive power, and speed-endurance capacity by implementing noninvasive procedures and sport-specific tests. We hypothesized that agility, speed, explosive power, and speed-endurance capacity might be maintained or increased by an individualized home-based training program. Eleven adolescent athletes participated in our study; they executed three tests before the coronavirus outbreak and 13 weeks later, after the pandemic curfew. We used the SpeedCourt System to assess the spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 22 publications
3
11
0
Order By: Relevance
“…Additionally, in a soccer study [40], no differences in CMJ height values were noted, although decreased peak CMJ power output values in elite soccer players were observed. On the contrary, Grazioli et al [23] demonstrated decreased CMJ height values in professional soccer players, whereas Parpa and Michaelides [38] and Pucsok et al [39] reported similar results to those presented here in professional and adolescent soccer players, respectively; however, both studies employed a home training protocol consisting of bodyweight exercises (including plyometric exercises), thus potentially masking the net effects of training cessation. Moreover, changes in the neuromuscular system during growth and maturation (specifically, increases in muscle size, pennation angle, fascicle length, tendon stiffness, and motor unit recruitment) have been reported to lead to enhanced performance related to explosive actions [41].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Additionally, in a soccer study [40], no differences in CMJ height values were noted, although decreased peak CMJ power output values in elite soccer players were observed. On the contrary, Grazioli et al [23] demonstrated decreased CMJ height values in professional soccer players, whereas Parpa and Michaelides [38] and Pucsok et al [39] reported similar results to those presented here in professional and adolescent soccer players, respectively; however, both studies employed a home training protocol consisting of bodyweight exercises (including plyometric exercises), thus potentially masking the net effects of training cessation. Moreover, changes in the neuromuscular system during growth and maturation (specifically, increases in muscle size, pennation angle, fascicle length, tendon stiffness, and motor unit recruitment) have been reported to lead to enhanced performance related to explosive actions [41].…”
Section: Discussionsupporting
confidence: 75%
“…Jumping ability, assessed through the CMJ performance, also showed a significant increase (4.96%). Previous research attempting to investigate the effects of the COVID-19 confinement period on vertical jumping performance has yielded equivocal results [23,35,[37][38][39][40]. In the studies by Spyrou et al [35] and Cohen et al [37] in elite futsal and soccer players, respectively, CMJ height values remained unchanged, yet differences in eccentric and landing phase kinetic variables were observed.…”
Section: Discussionmentioning
confidence: 96%
“…Detraining during the transition period caused significant performance impairments in a number of physiological and performance measures such as VO2max, time to exhaustion, repeated-sprint ability and Yo-Yo test intermittent-running performance [2,7,8,21]. Moreover, previous studies showed that a structured home-based exercise program during the COVID-19 lockdown was effective in maintaining or improving physical fitness measures such as countermovement jump performance, an indicator of lower extremity explosive strength in elite handball players [22], and youth soccer players [23]. In another study, it was stated that after a 32-week detraining period, caused by the COVID-19 pan-demic lockdown, significant improvements were observed in neuromuscular parameters (vertical jump height, agility, and linear sprints) of young soccer players, depending on maturation-related adaptations [11].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the home-based exercise performed by both groups during this period was partially sufficient, and that the detraining caused by the COVID-19 lockdown on the MAS was possibly mitigated. Pucsok et al [23] found that the endurance capacity of young soccer players was moderately deteriorated after completing a 13-week home-based training routine during the COVID-19 lockdown. In additon, recent studies stated that cardiorespiratory endurance or VO2max, determined by the maximum mean velocity reached in a multistage 20-metre shuttle run test, was decreased in elite handball players [24], youth soccer players [4,25], female soccer players [26], and professional soccer players [22] due to non-specific and insufficient stimuli caused by a home-based exercise program during the COVID-19 lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…Limit the capacity to 6 players at a time, minimizing the time they stay in the facility. Physiotherapy areas: a person in charge is appointed to ensure that whenever this area is accessed, everyone wears a mask and that of good health and particularly in groups of elite athletes who are often subjected to extraordinary disease prevention measures [14][15][16][17][18][19][20][21]. Those publications generally refer to the impact of the disease specifically on the performance of specific athletes and do not include the impact of COVID on a large sports institution as a whole [22].…”
Section: Ii) Preventive Management Criteria For Coexisting Population...mentioning
confidence: 99%